The Implementation of Community Empowerment Model as a Harmonization in the Village Traumatized by Terrorism Case - Sulaiman, Adhi Iman; Masrukin, Masrukin; Suswanto, Bambang (Jurnal Ilmiah Peuradeun, 2019)
There is a negative stigma toward Islamic boarding school (Pesantren) in the village suspected as supporting radicalism and the place of terrorist linked to bomb-blasting events in Indonesia between 2000-2017. The research used qualitative method of participatory learning action (PLA). Data were collected through interviews, and documentation, observation and focus group discussions and use participatory analysis technique. Informants heve been purposively selected namely community and religious leaders, groups of empowerment, village apparatus and Islamic boarding school management. The research took place in village of Pasuruhan, Cilacap in Central Java and village of Cikoneng, Ciamis in West Java. The results showed the community empowerment model could be mediation of trauma and disharmony through community-based economic activities of village resources potential, namely farming and livestock groups, business groups and cooperative business economy. The model of community empowerment should be developed to perform a comprehensive program ranging from the identification of the problem, the potential of human resources, natural resources and the economy of rural communities up to the analysis solution in the form of extension program, assistance and partnerships.